2022
DOI: 10.1002/cey2.172
|View full text |Cite
|
Sign up to set email alerts
|

TiO2 bunchy hierarchical structure with effective enhancement in sodium storage behaviors

Abstract: Bronze phase TiO2 [TiO2(B)] has great research potential for sodium storage since it has a higher theoretical capacity and ion mobility compared with other phases of TiO2. In this case, preparing porous TiO2(B) nanosheets, which can provide abundant sodium insertion channels, is the most effective way to improve transport kinetics. Here, we use the strong one‐dimensional TiO2 nanowires as the matrix for stringing these nanosheets together through a simple solvothermal method to build a bunchy hierarchical stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…However, the main challenge lies in the unsatisfactory kinetic behavior of the anode material when is assembled with the cathode material (typically active carbon, AC) [10,11]. For example, titanium dioxide (TiO 2 ) is considered as an ideal anode material due to its low cost, good cycle stability, high theoretical capacity (335 mAh g −1 ), non-toxicity and nearly zero-strain during charging and discharging process [12][13][14][15]. Nevertheless, the low conductivity (~ 10 -12 S cm −1 ) and the slow diffusion rate of Na + in TiO 2 severely limit its practical application.…”
Section: Introductionmentioning
confidence: 99%
“…However, the main challenge lies in the unsatisfactory kinetic behavior of the anode material when is assembled with the cathode material (typically active carbon, AC) [10,11]. For example, titanium dioxide (TiO 2 ) is considered as an ideal anode material due to its low cost, good cycle stability, high theoretical capacity (335 mAh g −1 ), non-toxicity and nearly zero-strain during charging and discharging process [12][13][14][15]. Nevertheless, the low conductivity (~ 10 -12 S cm −1 ) and the slow diffusion rate of Na + in TiO 2 severely limit its practical application.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison with the reported sodium‐ion anodes (FeNx@C, FeP@NC, Bi 2 Te 3 @ppy, TiNbO 5 @rGO, etc. ), [ 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ] the 1T’ Re 0.75 V 0.25 Se 2 electrode has very big advantages in ultra‐high rate capacity and long‐term cycling stability (Figure 3g ).…”
Section: Resultsmentioning
confidence: 99%
“…In comparison with the reported sodium-ion anodes (FeNx@C, FeP@NC, Bi 2 Te 3 @ppy, TiNbO 5 @rGO, etc. ),[44][45][46][47][48][49][50][51][52][53] the 1T' Re 0.75 V 0.25 Se 2 electrode has very big advantages in ultra-high rate capacity and long-term cycling stability (Figure3g).The reaction kinetic analysis based on CV curves was carried out at increasing sweep rates (0.2 to 1.0 mV s −1 ) to provide insight into the high-rate and long-life capabilities. As demonstrated in Figure4a, the pairs of cathodic and anodic peaks are well maintained with the increasing scan rate, suggesting a good reversible reaction in the 1T' Re 0.75 V 0.25 Se 2 electrode.…”
mentioning
confidence: 99%
“…A comparative first-principles study showed that TiO 2 (B) can reduce the formation energy and provide the most favorable sites for Na + insertion compared with anatase and rutile TiO 2 . Theoretically, TiO 2 (B) possesses a high capacity of 335 mAh g –1 and exhibits fast pseudocapacitance behavior . However, the practical capacity of TiO 2 (B) for Na + storage is still not high enough, and its semiconductive characteristic also hinders the rate performance.…”
Section: Introductionmentioning
confidence: 99%
“…17 Theoret-ically, TiO 2 (B) possesses a high capacity of 335 mAh g −1 and exhibits fast pseudocapacitance behavior. 18 However, the practical capacity of TiO 2 (B) for Na + storage is still not high enough, and its semiconductive characteristic also hinders the rate performance. Some strategies such as heteroatom doping or incorporation of carbon into TiO 2 (B) have been adopted to improve its performance.…”
Section: Introductionmentioning
confidence: 99%